Effect of Product Quality on Brand Switching (Studies In Consumers Handbody Marina at the Faculty of Social Sciences and Law, Makassar State University) - Aulia, Nur; Akib, Haedar; Kasmita, Maya; Syarifuddin, Syarifuddin (Universitas Negeri Makassar, 2025)
Effect of Product Quality on Brand Switching (Studies In Consumers HandbodyMarina at the Faculty of Social Sciences and Law, Makassar State University). Thesis. Business Administration Study Program. Administration Science Department. Faculty of Social Sciences and Law. Makassar public university. Supervised by Haedar Akib and Maya Kasmita. This study aims to determine the effect of product quality on brand switching on consumers handbody Marina at the Faculty of Social Sciences and Law, Makassar State University. This study uses a type of quantitative research. To achieve this goal, the researchers used a collection technique through questionnaires, observation, and documentation. Sampling technique using non-probability sampling namely by method purposive sampling. The sample used in this study was 96 respondents. Data obtained from the results of analysis using the SPSS software program Statistic version 25 which consists of validity test, reliability test, normality test, simple linear regression analysis, correlation test product moment, and test the coefficient of determination. The results showed that the indicators used for each variable, namely product quality (X), were in the very high and variable categories brand switching (Y) is in the high category. This shows that the product quality variable has a positive and significant influence on brand switching on consumers hand body Marina at the Faculty of Social Sciences and Law, Makassar State University. As well as the coefficient of determination obtained shows that brand switching influenced by product quality of 68.2% and the rest is influenced by other factors. Keywords: Product quality, Brand Switching, Handbody Marina